THE EASTERN FLANK OF THE CASPIAN BASIN: SEDIMENTARY COMPLEXES AND SEDIMENTATION CONDITIONS IN THE EARLY-MIDDLE CARBONIFEROUS - Konyukhov A.I.; Baimagambetov B.K.; Kan A.N. (My University, 2006)
Carboniferous and Lower Permian Carbonate and terrigenous rocks with the total thickness of >4000 m serve as the productive units in the Paleozoic subsalt complex at the eastern flank of the basin surrounding the northern area of the present-day Caspian Sea (hereafter, Caspian Basin in the broad sense). In recent years, several large oil and gas-condensate fields were discovered in these rocks. The complexity of geological evolution of this region, which is situated at the junction between the East European Platform and the Ural orogen, as well as multiple changes of sedimentation conditions during the Middle and Late Paleozoic, are reflected in the diversity of types of terrigenous and carbonate sediments and their facies alterations. Reconstruction of these environments makes it possible to elucidate specific features of the location of reservoir rocks in vertical and horizontal sections, as well as regularities of variations in their filtration-capacitive properties. © Pleiades Publishing, Inc. 2006.
Keywords: Permian; Carboniferous; Paleozoic::Permian; Палеозой::Пермская; Paleozoic::Carboniferous; Палеозой::Каменноугольная